Compact MIMO antenna. Issue 6 (June 2016) - Kumar, Jayendra
ABSTRACT: In this letter, a miniature wide‐band 1 × 2 antenna is proposed. The proposed antenna has a wider impedance bandwidth, 70% and small size, 31 × 20 × 1.6 mm 3 . There is a good isolation between two antennas, below −15 dB in the operating band. A monopole configuration is used to achieve the wide‐band response and a mushroom type Electronics Band‐gap structure is incorporated between the two antennas to achieve better isolation. Proposed antenna is simulated using High‐Frequency Structure Simulator and a prototype is tested on Vector Network Analyzer. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1294–1298, 2016